Guidelines for practice : integrating practice-based experiences. - Billett, Stephen (Australian Learning and Teaching Council, 2011)
These guidelines aim to assist people teaching in higher education to make decisions about organising and integrating their students' experiences in practice settings (ie workplaces) to support their students to develop the capacities for making smooth transitions to their selected occupations upon graduation and be effective in those roles. They were produced as part of a project that sought to identify and appraise curriculum and pedagogic principles and practices for integrating learning experiences in practice and university settings.